PSMA-PET/CT-based Lymph Node Atlas for Prostate Cancer Patients Recurring After Primary Treatment: Clinical Implications for Salvage Radiation Therapy - Schiller, Kilian; Stoehrer, Lucia; Duesberg, Mathias; Borm, Kai; Devecka, Michal; Vogel, Marco M. E.; Tauber, Robert; Heck, Matthias M.; Rauscher, Isabel; Eiber, Matthias; Gschwend, Juergen E.; Duma, Marciana Nona; et al. (European Urology Oncology, 2021)
BACKGROUND: Many patients experience recurrence of prostate cancer after radical prostatectomy. OBJECTIVE: The aim of this study was to visually analyze typical patterns of lymph node (LN) involvement for prostate cancer (PC) patients with biochemical recurrence after radical prostatectomy and lymphadenectomy by creating a color-coded heat map using gallium-68 prostate-specific membrane antigen positron emission tomography (68Ga-PSMA-PET) imaging. Further, we evaluated which LNs were covered by the Radiation Therapy Oncology Group (RTOG) clinical target volume (CTV) contouring guidelines. DESIGN, SETTING, AND PARTICIPANTS: A total of 1653 68Ga-PSMA-PET/computed tomography (CT) datasets were screened retrospectively. After meeting the eligibility criteria, 233 patients with 799 LN metastases were included in our study. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: We created a comprehensive three-dimensional color-coded LN atlas. Further, the coverage of LN metastases by RTOG CTV was assessed and stratification for risk factors was performed. RESULTS AND LIMITATIONS: In the overall, mainly high risk, collective, complete coverage by the standard RTOG CTV was accomplished in 31.0% of all LN metastases. The vast majority of uncovered LNs are situated in the para-aortal, pararectal, paravesical, preacetabular, presacral, and inguinal regions. Concerning examined stratification factors, prostate-specific antigen (PSA) levels at the time of PET/CT imaging had the highest predictive value for extrapelvic metastatic LN spread. Every increase of 1 ng/mL in PSA raises the risk of metastases outside the CTV by a factor of 1.43. CONCLUSIONS: We developed the first LN atlas for patients with recurrent PC using a heat map technique, in order to illustrate hot spots of LN recurrence. The vast majority of detected LNs are not covered by a standard CTV as recommended by the RTOG. Application of the standard RTOG CTV for pelvic irradiation in the salvage setting for high-risk PC patients seems to be inappropriate. PATIENT SUMMARY: We visualized typical lymph node recurrence sites for patients after prostate cancer surgery.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Lymph node atlas; Prostate cancer; Prostate-specific membrane antigen positron emission tomography